Effects of a community‐driven water, sanitation, and hygiene programme on COVID‐19 symptoms, vaccine acceptance and non‐COVID illnesses: A cluster‐randomised controlled trial in rural Democratic Republic of Congo. Issue 9 (14th August 2022) - Croke, Kevin; Coville, Aidan; Mvukiyehe, Eric; Dohou, Caleb Jeremie; Zibika, Jean‐Paul; Ghib, Luca Stanus; Andreottola, Michele; Bokasola, Yannick Lokaya; Quattrochi, John Paul
Abstract: Objective: The government of the Democratic Republic of Congo (DRC) responded to COVID‐19 with policy measures, such as business and school closures and distribution of vaccines, which rely on citizen compliance. In other settings, prior experience with effective government programmes has increased compliance with public health measures. We study the effect of a national water, sanitation, and hygiene programme on compliance with COVID‐19 policies. Methods: Prior to the COVID‐19 pandemic, 332 communities were randomly assigned to the Villages et Écoles Assainis (VEA) programme or control. After COVID‐19 reached DRC, individuals who owned phones (590/1312; 45%) were interviewed by phone three times between May 2020 and August 2021. Primary outcomes were COVID symptoms, non‐COVID illness symptoms, child health, psychological well‐being, and vaccine acceptance. Secondary outcomes included COVID‐19 preventive behaviour and knowledge, and perceptions of governmental performance, including COVID response. All outcomes were self‐reported. Outcomes were compared between treatment and control villages using linear models. Results: The VEA programme did not affect respondents' COVID symptoms (−0.11, 95% CI −0.55 to 0.33), non‐COVID illnesses (−0.01, 95% CI −0.05 to 0.03), child health (0.07, 95% CI −0.19 to 0.33), psychological well‐being (−0.05, 95% CI −0.35 to 0.24), or vaccine acceptance (−0.04, 95% CI −0.19 to 0.10). There was no effect on village‐level COVID‐19 preventive behaviour (0.03, 95% CI −0.23 to 0.29), COVID‐19 knowledge (0.16, 95% CI −0.08 to 0.39), or trust in institutions. Conclusions: Although the VEA programme increased access to improved water and sanitation, we found no evidence that it increased trust in government or compliance with COVID policies, or reduced illness.